Penerapan model PJBL untuk meningkatkan numerasi materi bangun ruang pada siswa kelas IV SDN Peterongan - Novita Estyawati; Fine Reffiane; Sumiyatun (Jurnal Pendidikan Guru Profesional, 2025)
This research aims to improve the numeracy skills of class IV students at SDN Peterongan on spatial building material through the application of the Project Based Learn ing Model. The research method used is Classroom Action Research (PTK) involving collaboration between researchers and teachers as research partners. At the planning stage, researchers designa learning plan that includes learning objectives, material to be taught, activities to be carried out, and evaluations to be carried out. The Project Based Learning model is used as a student-centered learning approach through providing projects at the beginning of learning. The implementation of the Project Based Lea rning Model is carried out in 3 cycles. Observations are carried out to observe students' interactions, their involvement in learning, and changes in their understanding of comparison. Students' numeracy abilities are evaluated through evaluation scores. The research results show an increase in numeracy skills after implementing the Project Based Learning model. Learners show more active involvement in the project and there is interest. They also demonstrated a better understanding of spatial material, which was reflected in increased evaluation scores. Based on these findings, it is recommended that teachers and schools consider using the Project Based Learning model in teaching spatial building material to class IV students. Collaboration between researchers and teachers is also important in developing effective learning methods. Further research can be carried out to involve more schools and classes in order to expand the scope of the research.